Indonesian cultural policy in the reform era - Jones, Tod (Cornell University, Southeast Asia Program, 2012)
The breadth and scale of the changes since the fall of Suharto raise the question whether previous research on Indonesian cultural policy, characterized here as an authoritarian cultural policy model, is still relevant. After reviewing Suharto-era cultural policy, this article updates previous research by examining five changes: the immediate response of artists and media to Suharto's resignation; national cultural policy change; political decentralization and the growth of ethnic and local identity politics; the implications of decentralization for regional cultural policy making; and the effects of public morality debates. It finishes by assessing the continued relevance of the authoritarian cultural policy model and identifying four broad uses of culture that are driving diversity in cultural policy across administrations.